The Solution for the Behavioural Constellation of Deprivation: The Popular and Solidarity Economy. (September 2017) - Vilchez, Jose L.
Learned helplessness occurs when one is unable to escape from a painful or aversive experience is unable to be escaped from (Hiroto & Seligman, 1975). The organism learns that it is helpless in and accepts its loss of control in those situations. This point is taken into account to explain the behavioural constellation of deprivation (BCD), in which one finds it difficult to escape from poverty. A new philosophy of economy is gradually emerging in the form of the so-called Economía Popular y Solidaria (popular and solidarity economy [PSE]). In this economical perspective, all members of companies are equally stockholders and investors so that these initiatives carry the implication that the democratisation process now moves from the political dimension to the economic arena. The democracy practiced in those businesses enables individuals to develop high levels of self-esteem and fosters a sense of belonging to the group.